Successful Implementation of Information Systems in Public Sector Organizations - Ajeng Apridiyanti; Harry Suharman; Zaldy Adrianto (Universitas Padjadjaran, 2020)
This study aims to determine the success of the implementation of the Regional Financial Management Information System (SIPKD) in the Regional Work Unit (SIPKD) in the Sumedang District Government, by examining the effect of system quality, information quality and service quality on user satisfaction and its implications for net benefits. This study uses primary data from questionnaires given to leaders of agencies, operators, and administrators of SIPKD. The data analysis method used is path analysis. The results of this study indicate that the quality of the system, the quality of information, and the quality of service affect user satisfaction and impact on net benefits both partially and simultaneously. The results of this study contribute to adding literature on the implementation of information systems in public sector organizations, and influencing factors can be used as a reference for public sector organizations in assessing the application of information systems.